Current Cost Accounting: Its Aspects and Impacts (Book). - O'Connor, Melvin C.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "Current Cost Accounting: Its Aspects and Impacts," edited by Adolf J.H. Enthoven.